Analysis of mucR gene regulating biosynthesis of exopolysaccharides: implications for biofilm formation in Sinorhizobium meliloti Rm1021 - Rinaudi, Luciana Veronica (2010)
Bacterial surface polysaccharides are crucial for establishment of successful rhizobia-legume symbiosis, and in most bacteria, are also critical for biofilm formation and surface colonization. In Sinorhizobium meliloti, the regulatory protein MucR controls exopolysaccharide production. To clarify the relationship between exopolysaccharide synthesis and biofilm formation, we studied mucR expression under growth conditions that influence attachment to polyvinylchloride, developed a microtiter plate assay to quantify biofilm formation in S. meliloti strain Rm1021 and mutants defective in succinoglycan (EPS I) and/or galactoglucan (EPS II) production, and analyzed expression of EPS I and EPS II genes by quantitative reverse transcriptase-PCR. Consistent with previous studies of planktonic bacteria, we found that disruption of the mucR gene in Rm1021 biofilms increased EPS II, but reduced EPS I gene expression. mucR expression was not affected by environmental conditions that influence biofilm formation on polyvinylchloride, and biofilm formation by Rm1021 was independent of exopolysaccharide synthesis. Other factors on the Rm1021 cell surface, and growth conditions, presumably regulate attachment and/or growth as a biofilm on polyvinylchloride.